VOICE RECOGNITION FOR SECURITY PURPOSES - NOOR ROZALI, NOOR ROHAIZAD (Universiti Teknologi PETRONAS, 2007)
This report presents the implementation of Voice Recognition System for Security Purposes. The scope of study is to understand the existing algorithms and develop a brand new algorithm which is better in terms of its reliability and accuracy. It will be implemented in Matlab environment. The main objective of this project is to develop a newvoice recognition system that will have minimum error in identifying the speaker. The system was built by combining a speech recognition system with a speaker recognition system. For speech recognizer, the Dynamic Time Warping is used and for speaker recognizer, the Mel-Frequency Cepstrum Coefficients is used. The results show that thecombination of both algorithms has produced a robust Voice Security System.